2018
DOI: 10.1002/ange.201804481
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Total Structure Determination of an All‐Alkynyl‐Protected Gold Nanocluster Au144

Abstract: Total structure determination of a ligand‐protected gold nanocluster, Au144, has been successfully carried out. The composition of title nanocluster is Au144(C≡CAr)60 (1; Ar=2‐FC6H4‐). The cluster 1 exhibits a quasi‐spherical Russian doll‐like architecture, comprising a Au54 two‐shelled Mackay icosahedron (Au12@Au42), which is further enclosed by a Au60 anti‐Mackay icosahedral shell. The Au114 kernel is enwrapped by thirty linear ArC≡C‐Au‐C≡CAr staple motifs. The absorption spectrum of 1 shows two bands at 560… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…The popular Perdew−Burke−Ernzerhof (PBE) GGA functional has been the de facto choice for structural and energetic studies of atomically precise nanoclusters, due to a well-demonstrated balance of accuracy and computational cost. 6 DFT-PBE's famous successes include structure prediction for Au 25 (SR) 18 and Au 38 (SR) 24 that were confirmed by experiment. 6,7 In terms of the interaction between electrons and the nuclei, the effective core potentials or pseudopotentials including the scalar relativistic effects are routinely employed for cluster systems with heavy metals such as Au.…”
Section: Density Functional Theory In Cluster Researchmentioning
confidence: 91%
“…The popular Perdew−Burke−Ernzerhof (PBE) GGA functional has been the de facto choice for structural and energetic studies of atomically precise nanoclusters, due to a well-demonstrated balance of accuracy and computational cost. 6 DFT-PBE's famous successes include structure prediction for Au 25 (SR) 18 and Au 38 (SR) 24 that were confirmed by experiment. 6,7 In terms of the interaction between electrons and the nuclei, the effective core potentials or pseudopotentials including the scalar relativistic effects are routinely employed for cluster systems with heavy metals such as Au.…”
Section: Density Functional Theory In Cluster Researchmentioning
confidence: 91%
“…28 In this case, the gold precursor is reduced by sodium borohydride in the presence of thiolcontaining ligands. Depending on the synthesis parameters, the formed gold nanoparticles have a size of ∼2 nm, 28 i.e., close to the size of atom-sharp gold clusters like Au 102 (pMBA) 44 (pMBA = p-mercaptobenzoic acid), 29 Au 70 S 20 (PPh 3 ) 12 , 30 Au 144 (CCAr) 60 , 31 (AuAg) 267 (SR) 80 , 32 and (AuAg) 45 -(SR) 27 (PPh 3 ) 6 . 32 Copper-catalyzed azide−alkyne cycloaddition (CuAAC) has emerged as a popular bioconjugation tool in the past decade.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20 Wang et al have recently reported the single crystal structure of the cluster Au 144 (CCAr) 60 with a multishell structure, based on Mackay icosahedra. 21 Yan et al cocrystallized two alloyed clusters, that is, (AuAg) 267 (SR) 80 (1.65 nm) and (AuAg) 45 (SR) 27 (PPh 3 ) 6 (1.05−1.25 nm) and determined their structure by single-crystal X-ray diffraction. The larger cluster consists of four concentric icosahedral shells and has a fully metallic behavior (no band gap).…”
Section: ■ Introductionmentioning
confidence: 99%